2016
DOI: 10.1002/cae.21774
|View full text |Cite
|
Sign up to set email alerts
|

Flipping the classroom to improve learning with MOOCs technology

Abstract: The use of Massive Open Online Courses (MOOCs) is increasing worldwide and brings a revolution in education. The application of MOOCs has technological but also pedagogical implications. MOOCs are usually driven by short video lessons, automatic correction exercises, and the technological platforms can implement gamification or learning analytics techniques. However, much more analysis is required about the success or failure of these initiatives in order to know if this new MOOCs paradigm is appropriate for d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0
14

Year Published

2017
2017
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 43 publications
(36 citation statements)
references
References 20 publications
(18 reference statements)
2
18
0
14
Order By: Relevance
“…From these data, it is observed that learning is positively influenced by the flipped learning and OLE tools as evidenced the total effects of the model, reflecting this way its dependency. This finding is in line with previous research concerning the efficiency of the flipped classroom approach and the effectiveness of technological online resources in terms of the improvement in learning.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…From these data, it is observed that learning is positively influenced by the flipped learning and OLE tools as evidenced the total effects of the model, reflecting this way its dependency. This finding is in line with previous research concerning the efficiency of the flipped classroom approach and the effectiveness of technological online resources in terms of the improvement in learning.…”
Section: Discussionsupporting
confidence: 92%
“…There are many successful experiences in flipped classroom implementation in engineering courses that confirm benefits and effectiveness of this active learning strategy and some examples showing student satisfaction and grade‐improvement . Nevertheless, with some exception , research examining the acquisition or development of key competences using this active learning approach continues to be minimal, even though this is a crucial issue in higher education.…”
Section: Theoretical Framework and Literature Reviewmentioning
confidence: 99%
“…Concerning engineering education, the number of MOOCs about mathematics, physics, statistics, and computer programming is increasing more and more . For example, when using an online educational platform with students in a remedial physics course, Muñoz‐Merino et al showed that students improved their grades significantly using MOOC technology.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Due to recent improvements in technology (instant messaging), web pages (Massive Online Open Courses−MOOC websites), online learning platform (such as Moodle), and video recording programs (Camtasia, Screencast‐O‐Matic or QuickTime), several solutions have been introduced to the out of class or in class activities. For example, Muñoz‐Merino et al uses a 26‐module MOOC to students of basic physics course before attending the face‐to‐face classes or Hsieh et al use LINE, an instant messaging system, in flipped EFL (English as a foreign language) oral training.…”
Section: Introductionmentioning
confidence: 99%